2017
DOI: 10.1017/s0022215117000135
|View full text |Cite
|
Sign up to set email alerts
|

The effect of local application of insulin-like growth factor for prevention of inner-ear damage caused by electrode trauma

Abstract: Local insulin-like growth factor 1 application may protect hearing after cochlear implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…Our study’s hearing threshold shift was greater than other rodent-based CI experimental models [ 18 ]. Although the threshold shift values we obtained in the study were high, another study using the same length (5 mm) of electrode analog also reported high hearing threshold shifts of approximately 65 ± 27 dB [ 17 ].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Our study’s hearing threshold shift was greater than other rodent-based CI experimental models [ 18 ]. Although the threshold shift values we obtained in the study were high, another study using the same length (5 mm) of electrode analog also reported high hearing threshold shifts of approximately 65 ± 27 dB [ 17 ].…”
Section: Discussionmentioning
confidence: 72%
“…A monofilament 5/0 polypropylene suture (Ethicon ® , Raritan, NJ, USA) with a length of 5 mm was employed for the insertion [ 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Clinical trials demonstrate that IGF-1 can improve hearing after sudden sensorineural hearing loss [55] but is less effective in mitigating ototoxic drug-induced sensorineural hearing loss [56]. When used in combination with a cochlear implant, either as an eluting gelatin hydrogel coating the electrode [57] or placed locally on the round window membrane in the form of soaked porcine skin gelatin [58], IGF-1 demonstrated protection of the auditory brainstem response (ABR) thresholds and showed better histopathological scores compared to a cochlear implant electrode with no coating.…”
Section: Insulin-like Growth Factormentioning
confidence: 99%
“…Insulin-like growth factor Animal and human studies [55,57,58] Good results were achieved with SNHL; IGF-1-coated electrodes showed better ABR results when compared to controls.…”
Section: Neurotrophin-3mentioning
confidence: 99%
See 1 more Smart Citation